Debilitating colonialism through ethnographic user-oriented evaluation of a collaborative science ICL course - Ngoepe, L.J. (South African Journal of Higher Education, 2020)
One of the most striking features of colonialism in the education system of South Africa (SA) is the sustained use of English as a language of teaching. If university tuition is offered to students in a non-native language such as English, these institutions inadvertently shoulder the responsibility of meeting the language needs of the students. As a response to the hegemony of English in Higher Education (HE), attempts made to meet the language needs of students in tertiary institutions are manifest in different approaches employed by universities, such as Integrating Content and Language (ICL) to support non-native speakers of English, in English media universities. It is thus vitally significant that courses offered in a number of countries be perennially evaluated to determine whether they are fit for purpose. The salience of evaluating input collected from a cohort of students who attend these courses cannot be overemphasised, hence a discussion of a student user-oriented evaluation of an integrated science content and language course taught collaboratively in one of the South African universities.